VARIATION IN STOCK OF PACIFIC RUDDERFISH (Upeneus japonicus, Houttuyn, 1782) AT THE VIETNAM-CHINA SHARED ZONE FOR FISHING IN THE GULF OF TONKIN FROM 2013 TO 2015 - Nhuan, Mai Cong; Bat, Nguyen Khac (Vietnam Journal of Marine Science and Technology, 2017)
Bensasi goatfish is one of the main target species of otter trawling and bottom gill net fishing at the Vietnam- China shared zone for fishing in the Gulf of Tonkin. The catabolism and anabolism values (a, b) of the length-weight relationship equation were estimated to be from 0.013×104 - 0.026×104 and 2.07 - 2.10 respectively. The length at first maturity of the female was 126 mm and that of the male was 116 mm. The average of fishing productivity of this species varied from 0.12 kg/h to 0.40 kg/h during the investigation (2013 to 2015). The density, presented in biomass per area unit, ranged from 4.22 kg/km2 to 12.40 kg/km2. The total stock size was estimated to vary from 1,134 tonnes to 3,360 tonnes with an average of 2,271 tonnes. The estimated allowable catch was 1,135 tonnes.